2016
DOI: 10.1063/1.4958462
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Unambiguous comparison of many-electron wavefunctions through their overlaps

Abstract: A simple and powerful method for comparing many-electron wavefunctions constructed at different levels of theory is presented. By using wavefunction overlaps, it is possible to analyze the effects of varying wavefunction models, molecular orbitals, and one-electron basis sets. The computation of wavefunction overlaps eliminates the inherent ambiguity connected to more rudimentary wavefunction analysis protocols, such as visualization of orbitals or comparing selected physical observables. Instead, wavefunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Figure 18 compactly shows the resulting energies of the excited states on the vertical axis, with colored horizontal bars indicating the state character. The di erent TD-DFT results are correlated (gray lines) using overlap calculations [74,194].…”
Section: In Uence Of the Method: Exchange-and Correlation E Ects In [mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 18 compactly shows the resulting energies of the excited states on the vertical axis, with colored horizontal bars indicating the state character. The di erent TD-DFT results are correlated (gray lines) using overlap calculations [74,194].…”
Section: In Uence Of the Method: Exchange-and Correlation E Ects In [mentioning
confidence: 99%
“…With the goal to ameliorate this situation, an automatic procedure to analyze wave functions as well as electron densities has been recently designed, providing a variety of visual and quantitative exploration methods for excitedstate computations [70][71][72][73][74]. This comprehensive toolbox has shown to be useful whenever a large number of excited states is to be analyzed, e.g., ensemble calculations of spectra, trajectory simulations, or higher excited states [75][76][77][78].…”
Section: Introductionmentioning
confidence: 99%
“…The character of the involved states, shown in Figures 6c, was analyzed by calculating wave function overlaps to the states at the equilibrium geometry; these overlaps allow to compare states for hundreds of calculations without individually inspecting the orbital and expansion coefficients. 57 This analysis showed that for the large majority of sampled geometries (Figure 6c), S 1 has ππ * character and S 2 has n O π * character, whereas for the higher states the character varies with geometry, e.g., the πσ * state which is distributed between the S 2 -S 5 . Comparing the spectrum to experimental spectra, we find that the MS-CASPT2 calculations qualitatively reproduce the first absorption band of 5BU, but the sampling has shifted the peak to slightly lower energies than those predicted experimentally.…”
Section: Absorption Spectrummentioning
confidence: 93%
“…Computing the overlap between full electronic wave functions is a common practice to compare ESs at the same or different molecular geometries. [38][39][40]45] On the other hand, the nature of the ESs can also be described by inspecting only the nature of the "hole" and the "particle" entities. Indeed, computing the mono-electronic wave function overlap between NTOs has proven to be a robust procedure to compare ESs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the other hand, a vast amount of mono-electronic orbital overlaps is required to fully compute the many-electron wave function overlap. [38,39] Needless to say, this new formalism represents a remarkable advantage with respect to standard CI-based methods in terms of computational efficiency. Following our same line of thought, Sapunar and co-workers have very recently proven the superior computational efficiency of NTO-over CI-based algorithms for the computation of ESs wave function overlaps.…”
Section: Introductionmentioning
confidence: 99%